1933 Minn. Gen. Laws 231-33 - (:unkn) unknown (My University, 1933)
An Act Making It Unlawful to Use, Own, Possess, Sell, Control or Transport a "Machine Gun", as Hereinafter Defined, and Providing a Penalty for the Violation Thereof, ch. 190, §§ 1-3: Prohibited owning, controlling, using, possessing, selling, or transporting a machine gun.
Keywords: MACHINE GUN RESTRICTION